2012
DOI: 10.1097/sla.0b013e318254f5b9
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation Versus Clinical Recurrence Rate After Ventral Hernia Repair

Abstract: Reoperation rate for recurrence 41 months after primary umbilical/epigastric or incisional hernia repair underestimated overall risk of recurrence by four- to fivefolds. This study was registered in www.clinicaltrials.gov (NCT01325246).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
3
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 22 publications
4
84
3
8
Order By: Relevance
“…In one study, it was concluded that reoperation rate for recurrence underestimates the overall risk of a recurrence by fivefold for incisional hernias [31]. There is also a register in Sweden and in Germany with no formal publications yet.…”
Section: Registersmentioning
confidence: 99%
“…In one study, it was concluded that reoperation rate for recurrence underestimates the overall risk of a recurrence by fivefold for incisional hernias [31]. There is also a register in Sweden and in Germany with no formal publications yet.…”
Section: Registersmentioning
confidence: 99%
“…The development of an incisional hernia has an important impact on the patients' quality of life and body image [13]. Furthermore, the repair of incisional hernias still has a high failure rate with long term recurrence rates above 30 %, even when mesh repair is performed [14][15][16]. Optimising the surgical technique to close abdominal wall incisions using evidence based principles, holds a potential to prevent patients suffering from incisional hernias and the potential sequelae of incisional hernia repairs [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the population-based Danish Ventral Hernia Database the reoperation rate for recurrence is the primary outcome measurement as a ''surrogate for recurrence''. Helgstrand et al [31] demonstrated using a questionnaire and subsequent selective request for clinical follow-up that the reoperation rate underestimated the overall risk for recurrence by four-to fivefold. In the Herniamed registry patients are followed up using a questionnaire send to the patient at 1, 5 and 10 years [29].…”
Section: The Methods Of Follow-upmentioning
confidence: 99%